LINGUISTIC IDENTITY NEGOTIATION ON TIKTOK: GLOCAL PRACTICES OF INDONESIAN CONTENT CREATORS - Muhsyanur Muhsyanur; Setya Yuwana Sudikan; Mannivannan Murugesa (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2025)
This study examines how Indonesian content creators negotiate their linguistic identity on TikTok, striking a balance between global and local influences through glocalized practices. Drawing on qualitative content analysis of 75 viral videos and in-depth interviews with 15 creators, this research examines how code-switching, hybridized language forms, and culturally-specific expressions are strategically used to construct online identities. The study adopts a qualitative, interpretive research design that integrates digital ethnography, multimodal discourse analysis, and semi-structured interviews in order to capture both observable linguistic practices and creators’ own reflections on their language choices. The video corpus was selected through purposive sampling from Indonesian TikTok accounts with substantial audience engagement, representing diverse content genres, geographic regions, and sociolinguistic backgrounds. Each video was analyzed for lexical, grammatical, pragmatic, and multimodal features, including spoken language, captions, visual cues, and interactional elements, to identify recurring patterns of linguistic identity negotiation. The findings identify four negotiation strategies: strategic multilingualism, cultural-linguistic hybridization, performative authenticity, and audience-adaptive communication. These categories were developed through iterative coding and thematic analysis, supported by qualitative analysis software, allowing patterns emerging from the content to be systematically compared with insights from creator interviews. Interview data further illuminate the motivations behind creators’ linguistic decisions, their perceptions of audience expectations, and their awareness of platform affordances that shape communicative behavior. These strategies demonstrate how creators intentionally shift between standardized Indonesian, regional dialects, English, and emerging digital vernaculars to engage diverse audiences while maintaining cultural authenticity. The study indicates that TikTok provides a dynamic space where creators both challenge and reinforce linguistic hierarchies. Creators’ language practices are shown to be deeply intertwined with platform logics, including algorithmic visibility, temporal constraints, and multimodal affordances, which together influence how linguistic identities are performed and interpreted. By connecting local practices with global digital trends, Indonesian creators not only reflect the nation’s complex sociolinguistic landscape but also exercise cultural agency in shaping new forms of expression in transnational spaces. These findings are interpreted through the theoretical lenses of glocalization, sociolinguistic scaling, and digital linguistic citizenship, situating Indonesian creators within broader debates on language, power, and identity in digital communication. The findings contribute to understanding digital linguistic practices and highlight the Global South’s role in the evolving digital culture.